Disclosure of elevated amyloid status is not associated with long‐term suicidality in a preclinical AD trial - Grill, Joshua D.; Raman, Rema; Flournoy, Charlene; Ernstrom, Karin; Pierce, Aimee; Smith, Amanda; Rosenberg, Paul; Burns, Jeffrey; Karlawish, Jason; Aisen, Paul; Holdridge, Karen Chilcott; Mancini, Michele; et al. (Alzheimer's & dementia, 2025)
INTRODUCTION The long‐term implications of disclosing Alzheimer's disease (AD) biomarker information to cognitively unimpaired individuals are unknown. METHODS We compared participants who disclosed their elevated amyloid imaging result in a preclinical AD trial to those who disclosed a not elevated result and enrolled in an observational cohort that underwent parallel assessments. Our primary outcome was a score > 0 on the Columbia Suicidality Severity Rating Scale (CSSRS) at any visit; we also considered suicidal behaviors (CSSRS > 5). RESULTS Among 1707 total participants (68% elevated amyloid, mean [standard deviation] age 71.5 [4.7], 60% female, 90% non‐Hispanic White), followed for a mean 218 (74.1) weeks, there were no suicides and few indications of suicidal thoughts (n = 124 [7%]) or behaviors (n = 13 [<1%]). In a generalized estimating equation model controlling for covariates, we observed no effect of amyloid status on the primary outcome of CSSRS > 0 (odds ratio = 1.6, 95% confidence interval = 0.76, 3.37). DISCUSSION With a structured approach, brain amyloid results can be returned safely. Highlights The Anti‐Amyloid Treatment in Asymptomatic Alzheimer's study was among the first and largest studies to include biomarker disclosure in a population without cognitive impairment. Routine psychological assessment provided a novel assessment of the impact of disclosure in this sample. Learning an elevated brain amyloid result through a protocolized approach was not associated with suicidal thoughts or behaviors compared to a matched cohort who learned they did not have elevated brain amyloid. Future research will be needed to ensure similar safety in more real‐world settings.